The disadvantages of the administrative judiciary compensation claim as a model - (comparative study) - Salah Gatea, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The case for remuneration is one of the managerial cases that the adjudicator appreciates with wide powers and plans to review the harms coming about because of the organization’s action and spoken to by the regulatory choices given by it by its will and material activities, and obviously, it is planned for accomplishing the open intrigue; however, the issue isn’t without overabundances hurtful to other people. On its side, which requires a contest among it and those influenced by its movement, and this question is submitted to the legal executive to explain its decision with pay for its deficiency in that department, and this case is known as a "total claim suit" and requires the arrangement of an attorney and readies an underwriter to secure rights and change the harm, and appraising crafted by the organization and deciding its obligation on the off chance that it goes amiss from the way that the law has set for it. The organization implies the official developments in full. Nonetheless, the laws of the common help in Iraq didn’t manage the arrangements identified with the case of pay in the regulatory field and alluded it to the customary legal executive, and this is a stifling authoritative lack that must be focused on.